Factors Influencing the Quality of Life in Thai Cancer Patients Receiving Chemotherapy during COVID-19 Pandemic - Supawan Jaiboon; Arveewan Vittayatigonnasak (Nurse Media Journal of Nursing, 2023)
Background: The Coronavirus disease (COVID-19) pandemic has physical and mental impacts on cancer patients receiving chemotherapy and this can lead to a decline in their quality of life (QoL). Little is currently known about the factors that affect QoL among cancer patients in Thailand during the COVID-19 pandemic.Purpose: This study aimed to examine the factors influencing the QoL of cancer patients receiving chemotherapy during the COVID-19 pandemic.Methods: This descriptive cross-sectional study was conducted among 102 cancer patients undergoing chemotherapy recruited using a simple random sampling technique. Four instruments were used; 1) Demographic and clinical characteristics questionnaires; 2) the Thai Hospital Anxiety and Depression Scale (Thai HADS); 3) the Revised Thai version of the Multidimensional Scale of Perceived Social Support (r-Thai MSPSS); and 4) the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30 (EORTC QLQC-30, Thai version). Descriptive statistics and multiple linear regression were used for data analysis.Results:  According to the findings, the study demonstrated that depression had a statistically significant negative influence on QoL, physical functioning, and emotional functioning (B=-2.196, p=0.001; B=-2.630, p<0.001; B=-1.605, p=0.009, respectively). Similarly, anxiety exhibited a negative influence on emotional functioning, cognitive functioning, and social functioning (B= -2.593, p<0.001; B=-1.508, p=0.037). However, social support did not significantly influence QoL.Conclusion: The study underscores the negative impact of depression and anxiety on QoL, emphasizing the importance of addressing psychological well-being. While social support’s influence on QoL was not significant in this context, the research highlights the factors affecting cancer patients’ well-being during challenging times. These insights could inform interventions to enhance QoL and patient care.